Prime Minister's Decree No. 1455 of the year 2021 Amending the Minimum Limit Values of the Total Wages of the Employees and Workers of the State Agencies and the Service and Economic Public Authorities = قرار رئيس مجلس الوزراء رقم 1455 لسنة 2021 بتعديل قيم الحد الأدنى لإجمالي الأجر للموظفين والعاملين لدى أجهزة الدولة والهيئات العامة الخدمية والاقتصادية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic